Pengaruh aktivitas Belajar dan Minat Belajar Siswa terhadap Prestasi Belajar Bahasa Arab - Daliman Daliman; Mufrod Teguh Mulyo (Program Pascasarjana UNU Surakarta, 2023)
The objectives of this study are: 1) To determine the influence of learning activities on Arabic learning achievement. 2) To find out the influence of students' interest in learning on Arabic learning achievement. 3) To find out the influence of learning activities and student interest in learning on Arabic learning achievement. This research uses survey methods with quantitative approaches and correlational analysis techniques. Data were collected by questionnaire and documentation techniques. The target population in this study was all MTsN 1 Karanganyar students which amounted to 851 people. Meanwhile, the sample was 247 students. The results of the study: 1) Learning activities have been proven to affect the achievement of learning Arabic for MTsN 1 Karanganyar students for the 2021/2022 Academic Year. Since the calculated value of t is greater than ttable 2.535 > 1.969734, then H0 is rejected and H1 is accepted; 2) student’s interest of learning has proven to have an effect on the achievement of learning Arabic for MTsN 1 Karanganyar students for the 2021/2022 Academic Year. This is because tcount is greater than ttable 57.680 < 1.969734), then H 0 is rejected and H2 is accepted; 3) student’s learning activity and interest in learning have been shown to have a significant influence on the learning achievement of Arabic students of MTsN 1 Karanganyar Academic Year 2021/2022. This is because Fcounts 2661,664 with a table F value of 3,032. So that the value of Fcounts > Ftable or 2661.664 > 3.032. And a significant rate of 0.000 < 0.05, then H0 is rejected and H3 is accepted.